Seasonal Dynamics of Algal Communities and Key Environmental Drivers in the Subpolar Front Zone off Eastern Korea - Pyo Il Han; Hyun Soo Rho; Joo Myun Park; Beom-Sik Kim; Jong Won Park; Dongyoung Kim; Dong Young Lee; Chung Il Lee (Biology, 2025)
Located within the subpolar front (SPF) zone, the eastern coast of Korea is subject to frequent environmental changes on both spatial and temporal scales. In this study, we analyzed seasonal changes in the algal community structure and related environmental factors at two sites, Chodo (CD) and Sageunjin (SG), which were influenced by cold and warm-water masses, respectively, in the SPF zone. Sea surface temperature (SST) exhibited greater seasonal change in CD, whereas significant wave height was higher in SG. The salinity and nutrient concentrations decreased during summer and increased in winter at both sites. Seasonal shifts in the dominant species were distinct, with turf species positively correlated with SST dominating the intertidal zone of SG during winter, and canopy species were associated with nutrient concentrations dominating the intertidal zone of CD. Bryopsidales, which was positively correlated with the N:P ratio, dominated the SG subtidal zone in summer, whereas Fucales, which was positively correlated with the SST, dominated the CD subtidal zone. These results enhance our understanding of seaweed responses to environmental changes in SPF zones and provide a basis for predicting future changes in coastal ecosystems.